2000
DOI: 10.2134/agronj2000.924672x
|View full text |Cite
|
Sign up to set email alerts
|

Simulating Inbred‐Maize Yields with CERES‐IM

Abstract: Detasseling is the operation that consists of removing the tassels of the female plants prior to silk emergence CERES-Maize, which was designed for simulation of hybrid maize and pollen shed to prevent self-pollination. During this (Zea mays L.), cannot be applied directly to seed-producing inbred maize because of specific field operations and physiological traits of operation, several leaves are generally removed from inbred maize plants. We developed CERES-IM, a modified version the plants. Though male-steri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
2
3

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 25 publications
0
13
2
3
Order By: Relevance
“…Maximum light interception values registered in this study were low as compared with records obtained for hybrids cropped in a similar environment (Maddonni et al, 2001) but represented an expected level for inbred lines because of their usually reduced leaf growth (Rasse et al, 2000). Maximum light interception values registered in this study were low as compared with records obtained for hybrids cropped in a similar environment (Maddonni et al, 2001) but represented an expected level for inbred lines because of their usually reduced leaf growth (Rasse et al, 2000).…”
Section: Discussion Canopy Characteristics Light Interception and Bcontrasting
confidence: 56%
See 1 more Smart Citation
“…Maximum light interception values registered in this study were low as compared with records obtained for hybrids cropped in a similar environment (Maddonni et al, 2001) but represented an expected level for inbred lines because of their usually reduced leaf growth (Rasse et al, 2000). Maximum light interception values registered in this study were low as compared with records obtained for hybrids cropped in a similar environment (Maddonni et al, 2001) but represented an expected level for inbred lines because of their usually reduced leaf growth (Rasse et al, 2000).…”
Section: Discussion Canopy Characteristics Light Interception and Bcontrasting
confidence: 56%
“…In spite of the agreement between inbreds and results from hybrids in the initial response to N of leaf area production, no treatment reached the critical LAI in our experiments, with the concomitant disadvantage for light capture. Maximum light interception values registered in this study were low as compared with records obtained for hybrids cropped in a similar environment (Maddonni et al, 2001) but represented an expected level for inbred lines because of their usually reduced leaf growth (Rasse et al, 2000). The negative effects of low N availability on leaf senescence additionally conditioned light interception efficiency, particularly after flowering.…”
Section: Discussion Canopy Characteristics Light Interception and Bcontrasting
confidence: 51%
“…One's perception of model accuracy is highly dependent on scale. For example, Rasse et al (2000) pointed out that experimental plot data are not as buffered against pest damage and individual management errors as averaged county grain yields. They cited two contrasting studies: one that reported accurate grain yield simulation using averaged county grain yields (Kiniry et al, 1997) and another that reported poor simulation of year‐to‐year grain yield variability using research plot data (Otegui et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Leaves partially removed before completing expansion will continue growing. On the same date, leaf weight is reduced by 10.5% and stem weight by 5.0% (Rasse et al, 2000). On the day of male plant removal, the remaining plant population density is reduced according to the loss of male plants and the initial proportion of male and female plants in the fi eld (Table 1).…”
Section: Development Of Modifi Ed Ceres-maizementioning
confidence: 99%